The Effect of Time Delay on Dynamical Behavior in an Ecoepidemiological Model - Changjin Xu; Yusen Wu (Journal of Applied Mathematics)
A delayed predator-prey model with disease in the prey is investigated. The conditions for the local stability and the existence of Hopf bifurcation at the positive equilibrium of the system are derived. The effect of the two different time delays on the dynamical behavior has been given. Numerical simulations are performed to illustrate the theoretical analysis. Finally, the main conclusions are drawn.